Micronutrient homeostasis in plants for more sustainable agriculture and healthier human nutrition - Assunção, Ana G. L.; Cakmak, Ismail; Clemens, Stephan; González-Guerrero, Manuel; Nawrocki, Adam; Thomine, Sébastien (Oxford University Press, 2022)
The provision of sustainable, sufficient, and nutritious food to the growing population is a major challenge for agriculture and the plant research community. In this respect, the mineral micronutrient content of food crops deserves particular attention. Micronutrient deficiencies in cultivated soils and plants are a global problem that adversely affects crop production and plant nutritional value, as well as human health and well-being. In this review, we call for awareness of the importance and relevance of micronutrients in crop production and quality. We stress the need for better micronutrient nutrition in human populations, not only in developing but also in developed nations, and describe strategies to identify and characterize new varieties with high micronutrient content. Furthermore, we explain how adequate nutrition of plants with micronutrients impacts metabolic functions and the capacity of plants to express tolerance mechanisms against abiotic and biotic constraints. Finally, we provide a brief overview and a critical discussion on current knowledge, future challenges, and specific technological needs for research on plant micronutrient homeostasis. Research in this area is expected to foster the sustainable development of nutritious and healthy food crops for human consumption.